Chemical, Physical, and Sensory Characteristics of Simulation Chips Based Milkfish (Chanos chanos) and Kidney Beans Flour (Phaseolus Vulgaris L.) as a Protein Sources Snack - Bara Yudhistira; Danang Eristanto; Sigit Prabawa (Jurnal Teknologi dan Industri Pertanian Indonesia, 2019)
Chips is one of the most popular snack foods in the community. Chips still have some drawbacks in terms of uniformity of size and made from one type of raw material only, so it has not been able to increase the nutritional value. Protein is needed for growth especially in children. It needs diversification of food products to meet protein needs for children. Based on high protein content of milkfish and kidney bean flour then used as raw material in making simulation chips. This research use Completely Randomized Design (CRD) with one factor that is variation of milkfish and kidney bean flour formulation. The data were analyzed by One Way Anova with 95% significance level. The results of research showed the best formulation on F2 (35% milkfish meat : 65% kidney bean flour). The result of chemical analysis on F2 is moisture 3,44 %wb, ash 3,84 %db, fat 23,22 %db, protein 23,01 %db, carbohydrate 51,01 %db, FFA 0,39 %db, total calories 5,30 kcal/g and crude fiber 4,40 %db. While physical analysis at F3 that is hardness 7,61 N and wholeness 96,74 %. While on sensory analysis the most preferred value is F2